2006
DOI: 10.1242/jcs.02865
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular adenosine activates AMP-dependent protein kinase (AMPK)

Abstract: AMPK activity. These effects are blocked by 5Ј Ј-iodotubercidine (5Ј Ј-ITU), an inhibitor of adenosine kinase. Moreover, inhibition of adenosine transport through the concentrative adenosine plasma membrane transporter CNT2 with formycin B results in the blockade of adenosinemediated AMPK signaling. Extracellular adenosine is equally able to activate AMPK and promote ACC phosphorylation in liver parenchymal cell models in a manner that is also inhibited by 5Ј Ј-ITU. In summary, this study shows that adenosine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 49 publications
6
80
0
Order By: Relevance
“…A well documented intracellular effect of adenosine is the activation of AMPK [27] 11 and our results show that activation of AMPK reduces SERT activity. This result indicates the possibility of SERT regulation mediated by intracellular adenosine and AMPK.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A well documented intracellular effect of adenosine is the activation of AMPK [27] 11 and our results show that activation of AMPK reduces SERT activity. This result indicates the possibility of SERT regulation mediated by intracellular adenosine and AMPK.…”
Section: Discussionsupporting
confidence: 61%
“…Cells were treated for 1 day with AICAR, a known pharmacological activator of AMPK [27]. The results showed that AMPK activation reduced SERT activity; however, this effect was additive to the inhibition yielded by adenosine treatment (Fig.…”
Section: Page 9 Of 27mentioning
confidence: 93%
See 1 more Smart Citation
“…Previously, adenosine has been reported to be an effective activator of AMPK (17). As cordycepin is a structural analogue of adenosine, it is reasonable to speculate that it is also an AMPK activator.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, short-term (1-10 minutes) incubation of human endothelial cells (38) as well as rat liver and intestinal epithelial cells (39) with micromolar concentrations of adenosine or its precursor nucleotides triggered a transient activation of AMPK. However, the mechanisms of these acute effects may differ substantially from the chronic effects of adenosine on AMPK inhibition seen in our experimental settings.…”
Section: Discussionmentioning
confidence: 99%